Latex non-slip mat and preparation method thereof
By injecting gas into the preparation process of latex anti-slip pads to form micro bubbles, the problem of insufficient wear and scratch resistance of existing latex anti-slip pads is solved, and the wear and scratch resistance of the product is improved and environmentally friendly.
Patent Information
- Application Number
- CN202411461955.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-25
AI Technical Summary
The existing latex anti-slip pads have insufficient wear resistance and scratch resistance, making them difficult to promote and apply.
By mixing mixed latex liquid, gas dispersant and surfactant at high speed, and injecting gas during the stirring process, forming a slurry of micro-bubbles, spraying it on a mesh, and plasticizing it at 150-160°C, it is prepared The obtained latex anti-slip pad has good anti-slip, wear, scratch resistance and elasticity.
The wear resistance and scratch resistance of latex anti-slip pads are improved, which reduces the preparation cost, and the product is more environmentally friendly due to the use of degradable latex materials.
Smart Images

Figure CN119507224A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-skid pads, and in particular to a latex anti-skid pad and a preparation method thereof. Background Art
[0002] Anti-skid mats are widely used in bathrooms, kitchens, swimming pools and other places with water and easy to slip because of their good anti-skid properties. In particular, grid-shaped anti-skid mats are widely used because of their good wear resistance, good anti-skid properties, strong water permeability, and less slurry usage. Existing anti-skid mats usually use PVC as the base material and are prepared by foaming. Although the raw materials of PVC anti-skid mats are cheap, plasticizers need to be added during preparation. However, the added plasticizers are easy to precipitate during use, which is harmful to the human body. In addition, PVC is difficult to degrade and is not environmentally friendly. In addition, the plasticization temperature of PVC is high, and the energy consumption during preparation is high, which is not environmentally friendly.
[0003] Latex is widely used in mattresses and other cushions because it is biodegradable. However, latex is rarely used to make anti-skid mats, especially mesh anti-skid mats. This is because when latex is used to make mesh anti-skid mats, in order to facilitate slurry coating and hanging slurry, the viscosity of the latex needs to be between 4-6x10 4 mpa.s, however, after foaming, although the elasticity of the latex slurry of this viscosity can meet the requirements, its wear resistance and scratch resistance are insufficient, which limits its application and makes it difficult to promote.
[0004] It can be seen that the existing technology still needs to be improved and enhanced. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a latex anti-skid pad and a preparation method thereof, aiming to solve the defect that the anti-skid pad obtained by foaming latex as raw material in the prior art has insufficient wear resistance and scratch resistance.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A method for preparing a latex anti-slip mat, wherein the method comprises the following steps:
[0008] Step 1: Mix the mixed latex, gas dispersant, surfactant and water by high-speed stirring, and inject gas during the stirring process to disperse the gas in the slurry to form microbubbles;
[0009] Step 2: Measure the slurry viscosity. When the slurry viscosity is 4.0x10 4 mpa.s, stop stirring, apply the slurry on the mesh and scrape it flat;
[0010] Step 3: plasticizing at 150-160° C. to obtain a latex anti-slip mat.
[0011] In the preparation method of the latex anti-slip mat, in the step 1, by weight percentage, the added amount of the mixed latex liquid is 50-60%, the gas dispersant is 5-10wt%, the surfactant is 0.1-0.5%, and the balance is water.
[0012] In the preparation method of the latex anti-slip mat, the average particle size of the gas dispersant is 1500-3000 meshes.
[0013] In the preparation method of the latex anti-slip mat, the volume proportion of microbubbles in the latex anti-slip mat is 15% to 30%.
[0014] In the method for preparing the latex anti-slip mat, in step 1, the average diameter of the microbubbles is 0.01 to 1.00 mm.
[0015] In the preparation method of the latex anti-slip mat, the gas dispersant is selected from a combination of one or more of calcium carbonate, talcum powder, silica powder, silicon dioxide, natural zeolite and molecular sieve.
[0016] In the preparation method of the latex anti-slip mat, the mixed latex liquid includes natural latex and butadiene rubber.
[0017] In the preparation method of the latex anti-slip mat, the mesh cloth comprises grids and mesh holes, and the grids are square grids and are staggered with each other.
[0018] In the preparation method of the latex anti-slip mat, the side lengths of the grid and the mesh holes are both 3 to 6 mm.
[0019] A latex anti-slip mat is prepared by the preparation method of the latex anti-slip mat as described above.
[0020] Beneficial effects:
[0021] The invention provides a method for preparing a latex anti-skid pad, which uses a mixed latex liquid as a raw material, adds a gas dispersant and a surfactant, and injects gas during mixing to obtain a foam slurry with low viscosity, which is not only convenient for coating and scraping, but also has good anti-skid, wear resistance, scratch resistance and resilience after plasticization and molding. The preparation method has simple steps, is easy to implement, and has a low plasticization temperature, which can reduce costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a physical picture of the latex anti-slip mat provided by the present invention. DETAILED DESCRIPTION
[0023] The present invention provides a latex anti-slip mat and a preparation method thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail with reference to the following embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0024] The present invention provides a method for preparing a latex anti-slip mat, the method comprising the following steps:
[0025] Step 1: Mix the latex, gas dispersant and water by high-speed stirring, and inject gas during the stirring process to disperse the gas in the slurry to form microbubbles;
[0026] Step 2: Measure the slurry viscosity. When the slurry viscosity is 4.0x10 4 mpa.s, stop stirring to obtain foamy slurry, apply the slurry on the mesh and scrape it flat;
[0027] Step 3: plasticize at 150-160° C. to obtain a latex anti-slip mat.
[0028] In the preparation method, gas is injected into the slurry during preparation to form microbubbles, and then the slurry can be plasticized and formed with bubbles without adding a foaming agent, thereby improving the elasticity of the pad body; at the same time, the formed microbubbles can reduce the viscosity of the slurry, reduce the amount of water added, and make the slurry have better wear resistance and scratch resistance after forming; the added gas dispersant is an inorganic powder, which can be used as a nucleation material for capturing gas, prevent the gas from escaping during stirring, and make the gas more evenly dispersed in the slurry, so that the performance of the obtained latex anti-skid pad is more uniform; the added surfactant can mix the latex liquid better with water, and make the injected gas form more stable microbubbles to avoid rupture during scraping and plasticization. The preparation method has simple steps, is easy to implement, and has a low plasticization temperature, which is more energy-saving, and the prepared latex anti-skid pad is degradable, so it is more environmentally friendly.
[0029] In a preferred embodiment, the raw materials for preparing the latex anti-slip mat include, by mass percentage: 50-60% mixed latex, 1-10% gas dispersant, 0.1-0.5% surfactant, and the balance is water. The mixed latex is the main material of the slurry, and its solid content is about 55-65%. It is composed of natural latex, butadiene rubber, polyacrylamide, zinc oxide, potassium hydroxide, casein, anti-aging agent, ZDC accelerator and other additives. Its specific ingredients and proportions can be adjusted according to actual needs. Since it is a prior art, it will not be described in detail here. The mixed latex is degradable and is therefore more environmentally friendly than PVC. However, the mixed latex has a higher viscosity and is not convenient for scraping. Therefore, in the present preparation method, its viscosity can be reduced by adding water and injecting gas to meet the requirements of scraping. The gas The body dispersant is an inorganic powder, which can be selected from one or more of calcium carbonate, talcum powder, silica powder, silicon dioxide, natural zeolite, and molecular sieve. It is dispersed in the mixed latex liquid, can form gas cores to capture gas, prevent gas escape, and can make the gas dispersed evenly, so that the bubbles of the slurry are uniform after plasticization and molding; the surfactant can make the mixed latex liquid and water mix better, and can stabilize the bubbles to prevent the bubbles from bursting during coating; the water is used to dilute the mixed latex liquid and reduce the viscosity of the mixed latex liquid, so that the obtained mixed slurry has a suitable viscosity, which is not only convenient for coating, but also can adhere to the mesh without losing slurry.
[0030] Since the volume proportion of microbubbles and the diameter of microbubbles will affect the viscosity of the slurry and the elasticity of the pad after the slurry is formed, generally speaking, the greater the content of microbubbles and the smaller the diameter, the smaller the viscosity of the slurry will be, which can reduce the amount of water added, and the elasticity of the pad after the slurry is formed will be better, and the wear and scratch resistance will also be better; when the volume proportion of microbubbles is relatively small, due to its small effect on the viscosity of the slurry, a large amount of water needs to be added to adjust the viscosity, which will reduce the wear and scratch resistance of the pad after the slurry is formed, and due to the small number of microbubbles, the elasticity is also insufficient. In this regard, in order to obtain better elasticity, wear and scratch resistance, the volume proportion of microbubbles in the slurry is 1% to 30%, preferably 15 to 30%, and more preferably 20 to 25%, which can reduce the amount of water added. After plasticization and molding, the density of the pad is small, and the elasticity, wear resistance and scratch resistance are good.
[0031] In addition, the average diameter of the microbubbles will also affect the wear resistance and scratch resistance of the pad. Generally speaking, the smaller the diameter of the microbubbles, the denser the slurry formed, the less likely the gas will escape during the plasticizing and heating process, and the mechanical properties of the pad will be better and more uniform after the slurry is formed. In this regard, in a preferred embodiment, by making the average diameter of the microbubbles 0.01 to 1.00 mm, the slurry can be made dense and delicate, and it can be smoother and flatter when applied and scraped, and it can ensure that the microbubbles do not escape during the plasticizing process, so that the mechanical properties of the pad are not affected when the density decreases.
[0032] Since the particle size of the gas dispersant affects the formation of bubbles and the dispersibility in the slurry, the smaller the particle size of the gas dispersant, the smaller the diameter of the microbubbles formed, and the better the dispersibility. However, since the gas dispersant is an inorganic powder, when its particle size is small, it is easy to agglomerate, resulting in an increase in its actual particle size. In this regard, in a preferred embodiment, the average particle size of the gas dispersant is 1500-3000 mesh. Within this particle size range, it can be evenly dispersed in the slurry and can capture gas to form microbubbles with a smaller diameter, thereby improving the elasticity of the pad body and making the pad body have better wear resistance and scratch resistance.
[0033] In addition, in order to obtain a grid-shaped latex anti-slip mat, a mesh cloth with a special structure is required. The mesh cloth includes grids and mesh holes. The grids are square grids and are staggered with each other, that is, the grids are connected by corners, and adjacent grids are separated by mesh holes of the same size. Therefore, when applying the slurry, the slurry will only hang on the grid. After plasticization and molding, square anti-slip blocks are formed. These anti-slip blocks are combined together to form a grid-shaped anti-slip mat.
[0034] Since the size of the grid and mesh will affect the size of the anti-slip block, and also affect the interval between the anti-slip blocks. In order to ensure that the pad body has good anti-slip properties, the size of the grid and mesh should not be too large. Too large will easily reduce its anti-slip effect, while too small will easily cause the slurry to stick together and fail to form a lattice-shaped pad body, increasing the cost. As a preferred embodiment, the side lengths of the grid and mesh are both 3 to 6 mm. The grid and mesh of this size can prevent the slurry from sticking when applying and scraping, can form a lattice-shaped pad body, and have good anti-slip properties.
[0035] The second aspect of the present invention also discloses a latex anti-slip mat, which is prepared by the preparation method of the latex anti-slip mat as described above. It is lattice-shaped and has block-shaped anti-slip blocks. The anti-slip blocks are obtained by plasticizing latex and have good elasticity and anti-slip properties, and are good in wear resistance and scratch resistance.
[0036] To further illustrate the preparation method of a latex anti-slip mat provided by the present invention, the following examples are provided.
[0037] Example 1
[0038] A method for preparing a latex anti-slip mat comprises the following steps:
[0039] Step 1: Mix 55% of latex, 8% of calcium carbonate (with an average particle size of 2500 mesh), 0.3% of surfactant, and the balance of water by mass, stir at high speed to mix, and inject gas during stirring to disperse the gas in the slurry to form microbubbles;
[0040] Step 2: Measure the slurry viscosity. When the slurry viscosity reaches 4.0x10 4mpa.s, stop stirring, apply the slurry on the mesh cloth, the mesh holes and grids of which are square with a side length of 4mm, and scrape it flat;
[0041] Step 3: plasticizing at 156° C. to obtain a latex anti-skid pad, wherein the volume proportion of microbubbles in the anti-skid pad is 25%.
[0042] Example 2
[0043] A method for preparing a latex anti-slip mat comprises the following steps:
[0044] Step 1: Mix 50% of a latex solution, 10wt% of a natural zeolite (with an average particle size of 1500 mesh), 0.5% of a surfactant, and the balance of water by mass, and stir at high speed to mix, and inject gas during the stirring process to disperse the gas in the slurry to form microbubbles;
[0045] Step 2: Measure the slurry viscosity. When the slurry viscosity is 4.0x10 4 mpa.s, stop stirring, apply the slurry on the mesh cloth, the mesh holes and grids of the mesh cloth are square, the side length is 3mm, and scrape it flat;
[0046] Step 3: plasticizing at 150° C. to obtain a latex anti-skid pad, wherein the volume proportion of microbubbles in the anti-skid pad is 15%.
[0047] Example 3
[0048] A method for preparing a latex anti-slip mat comprises the following steps:
[0049] Step 1: Mix 60% of latex, 5% of molecular sieve (with an average particle size of 3000 mesh), 0.1% of surfactant, and the balance of water by mass, stir at high speed to mix, and inject gas during stirring to disperse the gas in the slurry to form microbubbles;
[0050] Step 2: Measure the slurry viscosity. When the slurry viscosity is 4.0x10 4 mpa.s, stop stirring, apply the slurry on the mesh cloth, the mesh holes and grids of which are square with a side length of 5mm, and scrape it flat;
[0051] Step 3: plasticizing at 160° C. to obtain a latex anti-skid pad, wherein the volume proportion of microbubbles in the anti-skid pad is 30%.
[0052] Comparative Example 1
[0053] A method for preparing a latex anti-slip mat, the steps of which are basically the same as those of Example 1, except that in step 1, 45% of latex liquid, 8% of calcium carbonate (with an average particle size of 2500 mesh), 0.3% of a surfactant, and the balance of water are mixed, and no gas is injected during stirring.
[0054] Comparative Example 2
[0055] A method for preparing a latex anti-slip mat, the steps of which are basically the same as those of Example 1, except that in step 1, no gas dispersant is added, the amount of water is increased accordingly, and the volume of microbubbles in the prepared latex anti-slip mat accounts for 11%.
[0056] Comparative Example 3
[0057] A method for preparing a latex anti-slip mat, wherein the steps are substantially the same as those of Example 1, except that in step 1, the volume of microbubbles accounts for 50%.
[0058] Comparative Example 4
[0059] A method for preparing a latex anti-skid pad comprises the following steps: mixing 45% of latex liquid, 5% of foaming agent and 50% of water by mass, stirring and mixing to obtain slurry, applying the slurry on a mesh, foaming and plasticizing at 155°C to obtain the latex anti-skid pad.
[0060] It should be noted that in Examples 1-3 and Comparative Examples 1-3, the compositions of the mixed latex, by mass, are: 100 parts of natural latex, 12 parts of butadiene rubber, 10 parts of polyacrylamide, 5 parts of antioxidant, 1 part of zinc oxide, 1 part of potassium hydroxide, 1 part of casein, and 1 part of ZDC accelerator.
[0061] It should also be noted that the slurry coating thickness of Examples 1-3 and Comparative Examples 1-4 is the same, and the scraper spacing is 3 mm.
[0062] Performance Testing
[0063] The latex anti-slip pads prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to performance tests, including static friction coefficient, wear resistance and scratch resistance tests, wherein the static friction coefficient was conducted according to standard ASTM-F609; the wear resistance and scratch resistance test was conducted according to ASTMD4966-12 (2016) standard, and the resilience test was conducted using an elasticity testing machine. The specific test results are shown in Table 1.
[0064] Table 1. Performance test results
[0065]
[0066] It can be seen from Table 1 that the static friction coefficients of Examples 1-3 are all relatively high, indicating that the latex anti-skid pad prepared by the method of the present invention has a good anti-skid effect, the wear rate is less than 1, indicating good wear resistance and scratch resistance, and the rebound resilience is between 11-18, indicating that the pad body has good elasticity.
[0067] The rebound resilience of comparative example 1 is poor, and the wear and scratch resistance is also lower than that of example 1. The main reason is that no gas is injected into the slurry. Therefore, in order to meet the needs of coating and scraping, the amount of mixed latex added needs to be reduced, which will lead to a decrease in wear and scratch resistance. At the same time, due to the injection of gas, the gas that can be formed by stirring is less, resulting in its poor rebound resilience.
[0068] The wear and scratch resistance of Comparative Example 2 is lower than that of Example 1, which may be because no gas dispersant is added. At the same time, due to the absence of gas dispersant, the injected bubbles are difficult to lock in the slurry and are prone to uneven distribution, resulting in a small amount of microbubbles in the pad body and poor resilience.
[0069] The wear and scratch resistance of Comparative Example 3 is poor, mainly because the volume proportion of microbubbles is too large. This shows that the content of microbubbles should not be too large.
[0070] The wear resistance, scratch resistance and resilience of Comparative Example 4 are relatively poor, which may be because the wear resistance and scratch resistance of the slurry that meets the coating and scraping performance will decrease after foaming.
[0071] It can be seen that the latex anti-skid mat prepared by the method of the present invention has excellent anti-skid, wear-resistant, scratch-resistant and resilience properties, can meet the needs of kitchens and bathrooms, and can be widely promoted and applied.
[0072] It is understandable that those skilled in the art can make equivalent substitutions or changes based on the technical solution and inventive concept of the present invention, and all these changes or substitutions should fall within the protection scope of the claims attached to the present invention.
Claims
1. A method for preparing a latex anti-slip mat, characterized in that: The method comprises the following steps: Step 1: Mix the mixed latex, gas dispersant, surfactant and water by high-speed stirring, and inject gas during the stirring process to disperse the gas in the slurry to form microbubbles; Step 2: Measure the slurry viscosity. When the slurry viscosity is 4.0x10 4 mpa.s, stop stirring, apply the slurry on the mesh and scrape it flat; Step 3: plasticizing at 150-160° C. to obtain a latex anti-slip mat.
2. The method for preparing the latex anti-slip mat according to claim 1, characterized in that: In the step 1, by weight percentage, the added amount of the mixed latex is 50-60%, the gas dispersant is 5-10wt%, the surfactant is 0.1-0.5%, and the balance is water.
3. The method for preparing the latex anti-slip mat according to claim 2, characterized in that: The average particle size of the gas dispersant is 1500-3000 meshes.
4. The method for preparing the latex anti-slip mat according to claim 1, characterized in that: In the latex anti-slip pad, the volume of microbubbles accounts for 15% to 30%.
5. The method for preparing the latex anti-slip mat according to claim 4, characterized in that: In step 1, the average diameter of the microbubbles is 0.01 to 1.00 mm.
6. The method for preparing the latex anti-slip mat according to claim 2, characterized in that: The gas dispersant is selected from one or more combinations of calcium carbonate, talc, silica powder, silicon dioxide, natural zeolite and molecular sieve.
7. The method for preparing the latex anti-slip mat according to claim 2, characterized in that: The mixed latex liquid comprises natural latex and butadiene rubber.
8. The method for preparing the latex anti-slip mat according to claim 1, characterized in that: The mesh cloth comprises grids and mesh holes, wherein the grids are square grids and are staggered with each other.
9. The method for preparing the latex anti-slip mat according to claim 8, characterized in that: The side lengths of the grid and the mesh holes are both 3-6 mm.
10. A latex anti-slip mat, characterized in that: The latex anti-slip mat is prepared by the preparation method of any one of claims 1 to 9.